INTERACTION EFFECT OF MOTIVATION TO ATTEND ON ATTENDEES’ PARTICIPATION OF FILM FESTIVAL - Mercy Busayo Bello; Amelia Jennifer Ofodu (Scholar Express Journal, 2024)
This study determined the relationship between motivation to attend and attendee’s participation of film festival in Port Harcourt. The study employed primary sourced data that were gotten from a structured questionnaire filled by the respondents. The Taro Yemene was deployed to determine the sample size of 350 respondents while the Spearman’s rank order correlation coefficient was deployed to test the hypotheses at 0.05 level of significance. The study utilized the SPSS 23 software to analyze the data. The study found that that there is significant relationship between content specificity, intellectual enrichment, socialization, escapism, prestige/social status and celebrity presence and attendee’s participation of film festival in Port Harcourt. The study concluded that motivation to attend amplifies attendee’s participation of film festival in Port Harcourt. Therefore, the study recommended that a unique film selection should ensue in film festivals to curate a diverse and unique selection of films that carter to different tastes and preferences and Interactive experience by offering immersive experiences, such as virtual reality exhibitions, workshops or masterclasses to encourage intellectual enrichment and complement film screenings
Keywords: Content Specificity; Intellectual Enrichment; Socialization